Effect of endothelin-1 receptor antagonists on skin fibrosis in scleroderma patients from the EUSTAR database. Issue 2 (May 2016) - Jordan, Suzana; Distler, Jörg; Maurer, Britta; Walker, Ulrich A.; Huscher, Doerte; Allanore, Yannick; Riemekasten, Gabriela; Distler, Oliver
Introduction: The aim of the study was to evaluate the effect of endothelin-1 receptor antagonists (ETRAs) on skin fibrosis in systemic sclerosis (SSc) patients from the (EULAR Scleroderma Trials and Research) EUSTAR cohort. Methods: SSc patients from the EUSTAR cohort with at least three visits (pre-study visit without ETRA treatment, baseline and follow-up visit with ETRA treatment) were included. The control group consisted of SSc patients with the same inclusion criteria, but without ETRA treatment. The primary endpoint was the comparison of the delta change of the modified Rodnan skin score (mRSS) between baseline and follow-up in the ETRA versus the control group. Results: Data on 75 ETRA treated (68 bosentan, 1 sitaxentan, 6 ambrisentan) and 969 control patients were included. The delta change of mRSS was not significantly different between the ETRA group and the control group (n = 969; 0 (-2-1) vs. n = 75; 0 (-2-1); p = 0.4). Similarly, subgroup analysis on patients with diffuse, extended SSc disease (mRSS ≥16) did not show differences in the delta change of mRSS between the ETRA group and the control group (n = 125; −1 [-7-0] vs. n = 23; −1 [-7-2], p = 0.8). Likewise, diffuse SSc patients with mRSS 7-21 at baseline, reflecting recently identified enrichment criteria for clinical trials, did not show any difference between the ETRA and the control group (n = 219; −1 [-3-1] vs. n = 27; −1 [-3-2]; p = 0.5). Conclusions: This controlled, observational, real-life cohort study with a large sample size did not show effects of ETRAs on skin fibrosis in patients with SSc.